Development of mappanretemme' qur'an media module to increase knowledge and attitude of prospective bridal couples regarding exclusive breastfeeding - Sabrina Yasin; Citra Kesumasari; Burhanuddin Bahar (Tamalanrea: Journal of Government and Development (JGD), 2024)
The Mappanretemme’ media module is a development of the previous module, which was developed into a website-based application that adapted the previous Mappanretemme’ module and enriched it with a food menu for breastfeeding mothers. This application was introduced under the name “SUN 4 Catin”. This study assessed the increase in knowledge and attitudes of prospective bride and groom couples after using the Mappanretemme’ Plus module. The quasi-experimental study used a one-group pre- and post-test research design, and sampling was conducted using simple random sampling. This study was conducted on 46 prospective brides and grooms in KUA Soreang District, Parepare City. The knowledge variable showed an increase in the good category before and after, with a percentage of 21.74%, and the less category experienced a decrease after, with a percentage decrease of 28.26%, and the Wilcoxon test results obtained p-value 0.005 (p<0.05), indicating that there was an increase in the prospective bride and groom's knowledge before and after education using the SUN 4 Catin application. For the attitude variable, there was an increase in the positive attitude category before and after, with a percentage of 11.22%, whereas, for the negative attitude category, there was a decrease in the attitude category before and after, with a percentage of 15.67%. The Wilcoxon test results showed a p-value 0.127 (p>0.05), indicating that there was no difference in the attitudes of prospective bride and groom couples regarding exclusive breastfeeding and lactation management using SUN 4 Catin application.